Miniature tissue microarrays for HercepTest® standardisation and analysis. Issue 11 (27th October 2004) - Gulmann, C; Loring, P; O'Grady, A; Kay, E
Abstract : Aims: To assess the practicality of using a miniature tissue microarray (TMA) with several examples of each HercepTest® score from 0 to 3+ as a control for routine HercepTest immunohistochemistry. Methods: A TMA was constructed from in house cases of breast cancer where HercepTest on the whole sections showed scores 0, 1+, 2+, or 3+. The TMA, which measured 5 × 5 mm, was designed with four rows (each representing scores 0, 1+, 2+, and 3+), with five 0.6 mm cores from separate cases. In all, 20 individual cases were represented and the TMA took less than one hour to construct. Fifty sequential 4 µm sections were cut from the TMA to maximise the number of available sections. They were stored at 4°C for 1–270 days and when a case needed HercepTest staining the section was added to the TMA tissue control slide. Results: All slides contained tissue spots and immunohistochemical staining was consistent throughout the time period. Conclusions: The miniature TMA with examples of all HercepTest scores described here is an ideal tissue control and can be used as a visual reference for scoring a case. Slides stored at 4°C could be used for up to 270 days.